Impact of Anticoagulant and Antiplatelet Use on Outcomes in Blunt Chest Injury. Issue 8 (August 2019) - Udekwu, Pascal; Roy, Sara; Stiles, Anquonette; Dibbert, Ashley; Nguyen, Megan; Rice, Victoria
The aim of this study was to evaluate the impact of prehospital antiplatelet and/or anticoagulant (APAC) use on treatment and outcomes in patients with severe blunt chest injury. Patients with three or more rib fractures and a hospital length of stay (LOS) > three days admitted from 2014 to 2015 were included. Demographics, mortality, complications, injuries, hospital and ICU LOS, use of blood products, and thoracostomy were studied. Of 383 patients, 27.4 per cent were on APAC medication. Patients on APAC were older ( P < 0.0001), had higher Glasgow Coma Score ( P < 0.0001), and had lower Injury Severity Score ( P < 0.0001) and total number of fractures ( P = 0.0013) than the non-APAC group. APAC was not a predictor of mortality with or without age adjustment. In multiple linear regressions, APAC did not predict an increased LOS. APAC patients did not demonstrate an increase in admission diagnosis or complication of hemothorax, blood transfusions, tube thoracostomy, tracheostomy, LOS, or mortality rates. Similar findings are present in the subgroup of patients studied with high kinetic energy mechanism of injury. Our study does not support the perceived morbidity of APAC therapy in patients with severe blunt chest injury.